A matter of teaching and relationships: determinants of teaching style, interpersonal resources and teacher burnout - Simões, F.; Calheiros, M. M. (Social Psychology of Education, 2019)
The present study tests a model of the interplay between teaching style determi- nants, interpersonal resources, and teacher burnout dimensions, controlling for teachers’ experience variables. Two-hundred and ninety-seven teachers in the Por- tuguese educational system teaching in a rural region participated in the research. Using a Structural Equation Modeling approach, the key finding of this study is that teacher interpersonal self-efficacy and teacher–student closeness partially mediated the connections between teacher epistemological sophistication and student misbe- havior and teacher burnout. Specifically, an increment of teacher depersonalization is associated with student misbehavior, when mediated by interpersonal self-efficacy and teacher–student closeness. Moreover, while greater attunement with students (meaning lower conflict) prevents emotional exhaustion caused by student misbe- havior, it also has costs in terms of lower professional accomplishment. Thus, in intense interpersonal settings like schools, teacher interpersonal resources, espe- cially teacher–student closeness and attunement, may not have an universal positive return for educators. Implications for future research are recommended, such as the replication of this model across urban and suburban settings. In addition, it seems warranted that teacher pre-service and service training readdress the topic of inter- personal resources as a means to improve teacher well-being, including its merits and limits.